Narcotic analgesic use of hospitalized patients with lung cancer in palliative care service - Hüseyin Can; Gülseren Pamuk; Hilal İkbal Bilyay; Esra Meltem Koç; Yusuf Cem Kaplan; Yüksel Küçükzeybek; Ahmet Alacacıoğlu (SERNEV, 2017)
Introduction: Greater than half of cancer patients suffer from the pain, which is the one of the major problems that disrupt the quality of life at, any time during the disease. Pain should be decreased as soon as possible and the maintenance treatment should be planned in these groups of patients. The World Health Organization (WHO) suggests the use of a three-step analgesic ladder approach including non-opioid, weak opioid and strong opioids according to the severity of the pain. However, the pain palliation can't be accomplished in more than 80% of patients because of the wrong thoughts of health professionals, patients and patients' relatives about narcotic analgesics.Methods: In this study 72 lung cancer patients, hospitalized between 29 July 2013 to 31 December 2015 at Izmir Katip Çelebi University Atatürk Education and Research Hospital Palliative Care and Support Service were assessed retrospectively about pain palliation.Results: Patients mean ages 61.2 ± 8.2 and 77.8% (56) were male, and 22.2% (16) were female. Patients applied with different complaints such as Inability to feed, pain, general condition disorders, shortness of breath and nausea and 27.8% (20) of patients had only admitted with pain. The median duration of hospital stay was 7 (2-45) days, which is the 18.1% of patients were not given any analgesics. 49.2% (29) of patients have second line treatment, 50.8% (30) had received third line treatment. Hospitalization indication and discharge status of the patients was statistically significant association between analgesic use (p = 0.002; p = 0.03).Conclusion: Cancer pain is the most common symptom affecting the quality of life negatively. Pain management should be well known by clinicians. Success in the treatment of pain patients linked to multidisciplinary approach include the whole psychological and social environment will be possible with the treatment applied by step approach.